x(x+2)=7(x+x+2)+71

Simple and best practice solution for x(x+2)=7(x+x+2)+71 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x(x+2)=7(x+x+2)+71 equation:


Simplifying
x(x + 2) = 7(x + x + 2) + 71

Reorder the terms:
x(2 + x) = 7(x + x + 2) + 71
(2 * x + x * x) = 7(x + x + 2) + 71
(2x + x2) = 7(x + x + 2) + 71

Reorder the terms:
2x + x2 = 7(2 + x + x) + 71

Combine like terms: x + x = 2x
2x + x2 = 7(2 + 2x) + 71
2x + x2 = (2 * 7 + 2x * 7) + 71
2x + x2 = (14 + 14x) + 71

Reorder the terms:
2x + x2 = 14 + 71 + 14x

Combine like terms: 14 + 71 = 85
2x + x2 = 85 + 14x

Solving
2x + x2 = 85 + 14x

Solving for variable 'x'.

Reorder the terms:
-85 + 2x + -14x + x2 = 85 + 14x + -85 + -14x

Combine like terms: 2x + -14x = -12x
-85 + -12x + x2 = 85 + 14x + -85 + -14x

Reorder the terms:
-85 + -12x + x2 = 85 + -85 + 14x + -14x

Combine like terms: 85 + -85 = 0
-85 + -12x + x2 = 0 + 14x + -14x
-85 + -12x + x2 = 14x + -14x

Combine like terms: 14x + -14x = 0
-85 + -12x + x2 = 0

Factor a trinomial.
(-5 + -1x)(17 + -1x) = 0

Subproblem 1

Set the factor '(-5 + -1x)' equal to zero and attempt to solve: Simplifying -5 + -1x = 0 Solving -5 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -1x = 0 + 5 Combine like terms: -5 + 5 = 0 0 + -1x = 0 + 5 -1x = 0 + 5 Combine like terms: 0 + 5 = 5 -1x = 5 Divide each side by '-1'. x = -5 Simplifying x = -5

Subproblem 2

Set the factor '(17 + -1x)' equal to zero and attempt to solve: Simplifying 17 + -1x = 0 Solving 17 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-17' to each side of the equation. 17 + -17 + -1x = 0 + -17 Combine like terms: 17 + -17 = 0 0 + -1x = 0 + -17 -1x = 0 + -17 Combine like terms: 0 + -17 = -17 -1x = -17 Divide each side by '-1'. x = 17 Simplifying x = 17

Solution

x = {-5, 17}

See similar equations:

| (2x+y)(3x+5y)= | | 15x^2+10=0 | | -4.5q+1.7=-25.8-2q | | 4x^2-23x-11=0 | | (b-8)/(8b-16) | | 8x-12+3x-21=4.5 | | S=5k+5vfork | | 4(1+3n)=8(n+5) | | 3p^2+10p+8=0 | | 8(1-4b)-(7b+8)=-4b-5b | | 233=33+x-22 | | 4x+3=68+x-1 | | 4p+5p+1=0 | | 8w-8+8=48+8 | | axb=-36 | | (-x-4)=6(9+6x)-206 | | 3(-9x-5)=3+3(8-7x) | | y^3=-25y | | -4(6-4x)=168+(8-9x) | | 9(5x-9)=7(3+4x)-153 | | 50000=300/x | | 4x-6=-32 | | 2x+14+3x-15=7 | | 5(t+2)=2(t+3) | | (2x-7)(x+3)(x-2)=0 | | (4x)+(3x-8)=90 | | x+x-20=54 | | 2x^2+2y^2+8x-12y+3=0 | | 8y+3=7y-7 | | 20-5/2 | | j^2+24j+23=0 | | 2(x-3)-4x=8-3(2x-1)+11 |

Equations solver categories